Sculpting micro-, meio-, and macrofauna - Maric, Filip; Poto, Margherita Paola; Zimmermann, Heike Jane; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To appreciate the biodiversity of the Arctic Ocean and ocean floor, with a particular focus on lesser-known species. What kind of micro- meio-, and macrofauna (species) live on the ocean floor and what do they look like? Learning objectives: In this activity, pupils will identify (one, two, or more) species living at or close to the Arctic Ocean floor and sculpt them using modelling clay. Through this activity, pupils will hopefully begin to understand difference between Arctic Ocean micro-, meio-, and macrofauna. Key words: Arctic ocean biodiversity, species, fauna.